Writing exile : the discourse of displacement in Greco-Roman antiquity and beyond - Gaertner, Jan Felix, 1976- (Mnemosyne, Supplements, 2007)
Exile and displacement are central topics in classical literature. Previous research has been mostly biographical and has focused on the three most prominent exiles: Cicero, Ovid, and Seneca. By shifting focus to a discourse of exile and displacement in early Greek poetry, Greek historiography, Cynicism, consolatory literature, Latin epic, Greek literature of the empire, and Medieval Latin literature, the present volume questions the notion of a distinct, psychologically conditioned 'genre' or 'mode' of exile literature. It shows how ancient and medieval authors perceive and present their exile according to pre-existent literary paradigms, style themselves or others as 'typical' exiles, and employ 'exile' as a powerful trope to express estrangement, elicit readerly sympathy, and question political power structures.